2008
DOI: 10.3102/0013189x08319571
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Excellence in Teacher Workforce and Equity in Learning Opportunities in South Korea

Abstract: Akiba, LeTendre, and Scribner (2007) identified two problems with mathematics education in the United States: (a) a shortage of qualified mathematics teachers and (b) unequal access to those teachers by students of high and low socioeconomic status. Akiba et al. called for further research on how South Korea and other countries have achieved excellence in their teacher workforces and equity in access to qualified teachers. They also called for research on what mediates the relationship between opportunity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 14 publications
0
56
0
Order By: Relevance
“…The high success of the South Korean students on international exams draws attention to the teacher training and teacher qualities. Indeed, much research (Angrist & Lavy, 1998;Boyd, Grossman, Lankford, Loeb & Wyckoff 2009;Kang & Hong, 2008) reveals the relationship between student success and teacher quality. Recent studies (Scheerens & Bosker, 1997) have revealed that the quality and methods of teaching impact student success more than the school environment.…”
Section: Introductionmentioning
confidence: 99%
“…The high success of the South Korean students on international exams draws attention to the teacher training and teacher qualities. Indeed, much research (Angrist & Lavy, 1998;Boyd, Grossman, Lankford, Loeb & Wyckoff 2009;Kang & Hong, 2008) reveals the relationship between student success and teacher quality. Recent studies (Scheerens & Bosker, 1997) have revealed that the quality and methods of teaching impact student success more than the school environment.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan and Korea, teachers are civil servants hired at the country or regional level. The central or regional governments assign teachers to schools that are in need of teachers and rotate teachers among schools periodically to guarantee the equal distribution of teachers within the region [39,40]. In many European countries, where teachers are also civil servants, governments can assign teachers to particular schools or compel teachers to move between schools if necessary [41].…”
Section: Factors Explaining Teacher Mobilitymentioning
confidence: 99%
“…They must enrol at one of ten national universities of education (gyodae) or two public universities and only one undergraduate department in a private women's university. As a result of this selective process, South Korea has one of the most highly qualified teaching forces, with nearly 100 per cent obtaining professional degrees and certification (N.-H. Kang & Hong, 2008). 3 In 2017, the fertility rate reached an all-time low of 1.05, an 11.9 per cent decrease from the previous year (Korea Times, 2018).…”
Section: Introductionmentioning
confidence: 99%